UI/UX Design of Academic Applications and Libraries at Universitas Islam Al-Azhar Based on Mobile App - Damar Giri Prada; M. Juniar Alfarizi; Aisyah Aryandani (Universitas Islam Al-Azhar Mataram, 2025)
The development of academic applications that integrate digital libraries and academic information systems is becoming increasingly important in higher education institutions. This study aims to design the User Interface and User Experience Design of a mobile-based application for Al-Azhar Islamic University that combines these two systems using the Design Thinking method. Through the stages of empathize, define, ideate, prototype, and test, user-centered insights are collected and translated into a functional and visually appealing prototype using Figma, Figma is used because of its advantages for simultaneous design. The survey results showed that most students had difficulty accessing academic materials and navigating existing platforms. The final prototype integrates academic and library functions with a consistent and user-friendly interface that aligns with the university's visual identity. The results show that the prototype meets user expectations in terms of clarity, usability, and shows potential for improving and developing academics. This study takes a new approach to integrating academic information systems and digital libraries into one mobile application through collaborative UI/UX design.